POTENSI BAKTERI ASAM LAKTAT PROBIOTIK INDIGENUS SEBAGAI ANTIDIARE DAN IMUNOMODULATOR [Potency of Indigenous Probiotic Lactic Acid Bacteria as Antidiarrheal Agent and Immunomodulator] - Made Astawan -; Tutik Wresdiyati -; Irma Isnafia Arief; Dwi Febiyanti - (Jurnal Teknologi dan Industri Pangan, 2011)
The aim of the study was to observe the ability of indigenous probiotic lactic acid bacteria (LAB) Lactobacillus plantarum 2C12 and Lactobacillus fermentum 2B4 as antidiarrheal agent in rats infected by Enteropathogenic Escherichia coli (EPEC), and also to observe their effect as immunomodulator (malonaldehyde level and proliferation of lymphocyte cell). A total of 90 male Sprague Dawley rats were used for this study and divided into 6 groups i.e.: (1) Negative Control (not infected with of EPEC), (2) LAB L. plantarum 2C12, (3) LAB L. fermentum 2B4, (4) LAB L. plantarum 2C12 + EPEC, (5) LAB L. fermentum 2B4 + EPEC, and (6) Positive Control (infected with EPEC). The treatment of LAB was undertaken from 1st-21st day, while infection of EPEC using 106 cfu/ml per day was undertaken during 8th -14th day. Groups administered with LAB L. plantarum 2C12 + EPEC, LAB L. fermentum 2B4 + EPEC, and positive control, showed decreased body weight during 12th-21st day. At the 21st day, positive control group underwent acute diarrhea (fecal water content was 68.2 % b/b). Statistical analysis with Duncan Test showed that the treatment given to six groups of rats gave significant effect (p<0.05) toward PER value, number of lymphocyte cells and malonaldehyde level in liver and kidney of the rats.